Simplify 12−4÷4/3+1.

1 answer

To simplify the expression, we follow the order of operations (PEMDAS/BODMAS).

First, we simplify within the parentheses:
4 ÷ 4/3 = (4 ÷ 4) × 3 = 1 × 3 = 3

Next, we can rewrite the expression as:
12 − 3 + 1

We can now add and subtract from left to right:
12 − 3 + 1 = 9 + 1 = 10

Therefore, the simplified expression is 10.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions